Lesi Erosif Mukosa Oral Sebagai Akibat Penggunaan Pasta Gigi Mengandung Sodium Lauryl Sulfate - Tenny Setiani Dewi (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
There are many sales promotions about dentifrices with various composititions nowadays, offered by several manufacturers. Public will be the main target consumers of these products and the choice lies upon their decision to become the user of these products.. Each human as a biological being, has different individual responses towards mechanical or chemical agent including material contained in dentifrices exposed by any; physical, mechanical or chemical means. In this case, white oral lesions were reported in a 34 years old man, due to the use of a dentifrice product that he has not been using before. The dentifrice contains Sodium Lauryl Sulfate (SLS), which is known as a detergent. The oral lesions detected, were surrounded by erythematous halo and mucosal erosions on his tongue. Sensitivity reaction has occurred and the patient chief complaints were disturbing sore of the tongue, on chewing and speaking The oral lesions were likely caused by the denaturating effect of the SLS, on the mucinal layer of the oral mucosal surface .Mucin is the main organic content that act as a visco-elastic material which protects the entire surface of the mucosa. It supposed to play an integrated role in the protection of the non-immune reaction of the mucosal surface. The oral mucosal epithelium might then be more exposed and vulnerable to any irritants and allergens, causing ulcerative lesions. Management provided, was cessation of SLS containing dentifrice, topical application of corticosteroids on the lesion, antiseptic mouthwash and multivitamin. The lesions disappeared within 2 weeks and the patient was suggested to use a non- SLS dentifrice as he did before.